School‐based health and nutrition interventions addressing double burden of malnutrition and educational outcomes of adolescents in low‐ and middle‐income countries: A systematic review - Sachin Shinde; Dongqing Wang; Gretchen E. Moulton; Wafaie W. Fawzi (Maternal and Child Nutrition)
Abstract School system is a promising platform for addressing all forms of malnutrition in adolescents. However, little is known about the impact of integrated school health and nutrition programmes on adolescent nutrition and educational outcomes in low‐ and middle‐income countries (LMICs). This systematic review sought to characterize school‐based health and nutrition interventions among adolescents in LMICs and analyze their effects on nutritional status and educational outcomes. Four databases were searched for studies evaluating school‐based health and nutrition interventions for adolescents in LMICs, reporting changes in either nutritional status or educational outcomes. A narrative synthesis was used to analyze and describe the evidence. Our review included 68 articles evaluating 58 interventions, of which a third had moderate to strong methodological quality. Forty‐two studies evaluated single‐domain interventions, while 26 evaluated multi‐component interventions. A third of all interventions were based on a theoretical framework. Three‐fourths of the interventions were shorter than 11 months, which may make identifying their effect difficult. The results of the effectiveness of these interventions were mixed and inconsistent across intervention types. Sixteen out of 21 studies evaluating multi‐component interventions and 12 out of 23 studies evaluating nutrition education reported improving nutritional or diet‐related outcomes. One out of six studies reported positive effects on educational outcomes. Our review has identified that research needs include: a greater inclusion of theory‐based approaches to guide the implementation of interventions; more studies of integrated interventions that involve parents and the wider community in LMICs; and extension of outcomes beyond nutritional status to include educational outcomes.